Kemampuan Penalaran Matematis Siswa dalam Menyelesaikan Soal Cerita Matematika - Millah, Dini Izzatul; Hidayah, Shofia (Papanda, 2025)
Mathematical reasoning ability is one of the essential competencies that students must possess in order to understand, analyze, and solve mathematical problems logically and systematically. This study aims to describe the mathematical reasoning ability of Grade VIII students at MTs Nurul Jadid in solving mathematical word problems. The research employed a descriptive qualitative approach with six student subjects, grouped into high, medium, and low ability categories. The research instruments consisted of test questions and interview guidelines. In this study, the data analysis techniques included data reduction, data presentation, and conclusion drawing. The indicators of mathematical reasoning included: (1) making conjectures, (2) formulating problem-solving strategies, (3) performing calculations, and (4) drawing conclusions. The results showed that high-ability students (T1 and T2) were able to meet all four indicators accurately; they could clearly make conjectures, determine problem-solving strategies, perform calculations accurately and systematically, and draw logical conclusions. Medium-ability students (S1 and S2) met only some indicators. Subject S1 fulfilled two indicators, namely making conjectures and determining problem-solving strategies. Subject S2 was only able to make conjectures but failed in the other indicators. Meanwhile, low-ability students (R1 and R2) encountered difficulties in almost all indicators. Although both subjects were able to make conjectures, they were unsuccessful in formulating strategies, performing calculations, and drawing logical conclusions. In some cases, no answers were found at all on their worksheets, indicating complete confusion in starting the problem-solving process.